A new bilaterally injured trilobite presents insight into attack patterns of Cambrian predators - Ruiwen Zong; Russell D.C. Bicknell (PeerJ, 2022)
Durophagous predation in the Cambrian is typically recorded as malformed shells and trilobites, with rarer evidence in the form of coprolites and shelly gut contents. Reporting novel evidence for shell-crushing further expands the understanding of where and when in the Cambrian durophagy was present. To expand the current documentation and present new records of malformed trilobites from the Cambrian of China, we present an injured Redlichia (Pteroredlichia) chinensis from the lower Cambrian Balang Formation, western Hunan, South China. The specimen has two distinct injuries along the thorax. The injuries show different degrees of regeneration, suggesting that the specimen was attacked twice. We propose that the individual may have been targeted more readily for the second attack. This predatory approach would have been highly energy efficient, maximizing net energy gain during the attack.